Corrigendum - Editorial (Vojnosanitetski Pregled)
In the original article by Raša Mladenović, Leonardo Pereira, Filip Djordjević, Zoran Vlahović, Kristina Mladenović, Andrijana Cvetković, Brankica Martinović, Jovan Mladenović, Julie Popovski. The use of mobile-aided learning in education of local anesthesia for the inferior alveolar nerve block/ Primena učenja putem mobilnih uređaja u edukaciji mandibularne anestezije. Vojnosanit Pregl 2020; 77(8):839-43. (https://doi.org/10.2298/VSP180622154M), the first name of the second author was misspelled as Leonardo instead of Leandro. The correct name of the second author should be Leandro Pereira, so the list of the authors should have read: Raša Mladenović, Leandro Pereira, Filip Djordjević, Zoran Vlahović, Kristina Mladenović, Andrijana Cvetković, Brankica Martinović, Jovan Mladenović, Julie Popovski. We apologize for any inconvenience that this may have caused. Link to the corrected article 10.2298/VSP180622154M